Law Enforcement Trauma: Phenomenological Study - Protecting the U.S. Capitol on January 6th - Johnson, Geoffrey (Advances in Social Sciences Research Journal, 2025)
This qualitative study analyzes the public testimony of four law enforcement officers who defended the U.S. Capitol during the January 6, 2021, insurrection. Using thematic analysis of their statements presented to the House Select Committee, the research unmasks four themes: contested identity and ideas of patriotism (Who’s a Traitor); existential vulnerability (Being Killed by My Own Weapon); prolonged psychological suffering (Recovery from Trama); and institutional abandonment (Betrayal by Congressional Authorities). The findings illuminate concepts of ethical harm embedded within law enforcement, revealing how institutional neglect and politized aggression can exacerbate post-traumatic stress. This study advocates trauma-informed care, public acknowledgement, and ethical accountability as essential components of recovery and reform. These officer’s lived experiences offer a humanizing lens through which to reassess core democratic values and the treatment of those who take oaths to protect and serve our nation.